Twitter as political acclamation - Hegelich, Simon; Dhawan, Saurabh; Sarhan, Habiba (Frontiers in Political Science, 2023)
The idea of acclamation has been used to understand political phenomena by a range of 20th century thinkers and has been recently revived and extended by Agamben (2011). Dean (2017) recently used such a perspective of political acclamation to analyze social media and pointed out that the way political communication works on social media is a new form of acclamation. However, if the notion of social media as acclamation is to be fruitful, it should be closely connected to inherent features of social media as technology and should be available to empirical analysis. To do so, this study follows a mixed-method approach. First, we offer a theoretical analysis of acclamation and how it links to each of the constituent parts of social media. Next, we build upon this theoretical analysis to study acclamation and social media as a matter of empirical data analysis using the methodological toolkit of computational social science. Our findings expand the idea of social media as acclamation and prove its relevance to the current political discourse.